FOREIGN LANGUAGE CLASSES FOR PROFESSIONAL PURPOSES AT UNIVERSITY: DEVELOPMENT OF FLUENCY - Alla Durdas; Tetiana Harbuza; Valentyna Borshchovetska; Yuliia Radchenko; Hanna Starosta (Borys Grinchenko Kyiv Metropolitan University, 2024)
This article explores the challenges and methods related to developing fluency in a foreign language for professional purposes at university. It deals with the difficulties faced by both teachers and students in maneuvring through linguistic complexities, overcoming language barriers and mastering specialized terminology relevant to various professional fields. The article highlights the importance of a targeted approach that fosters not only linguistic proficiency but also a deep understanding of cultural distinctions and communication norms, specific for various industries. Additionally, it investigates pedagogical strategies and methods aimed at enhancing fluency acquisition at classes of foreign language for professional purposes. Key challenges in the process of developing fluency at classes of foreign language for professional purposes have been highlighted: linguistic complexity; language barriers; cultural nuances; motivation and engagement; limited practice; fear of making mistakes; individual learning styles and preferences; assessment and feedback. Possible methods for developing fluency have been considered: communicative language teaching; immersion into a targeted language; organizing language exchanges; using authentic materials; role-playing and simulation; fluency-oriented activities, unassisted repeated reading and audio-assisted repeated reading; digital storytelling; vlogging, etc. By highlighting challenges and a certain number of existing methods of fostering fluency development, the article stresses on the necessity to provide regular feedback and correction of mistakes. Creating a favorable, engaging, interactive, and stress-free learning environment in the classroom has been stressed as the key prerequisite.